CRISPR-Cas9 gene-editing to assess the role of RF-amide−related peptide 3 in ovine seasonal breeding - C. Richard; A. Allais-Bonnet; M. André; V. Gelin; M-C. Deloche; D. Thépot; E. Canon; L. Laffont; O. Dubois; P. Congar; O. Lasserre; T. Aguirre-Lavin; et al. (Animal)
Seasonal breeding is an adaptive strategy that ensures the birth of the offspring during the best time of year and allows energy saving in times of food scarcity and adverse environmental conditions. At temperate and polar latitudes, photoperiod is the main synchroniser of seasonal functions, which exerts its action through melatonin. Within the pars tuberalis of the anterior pituitary, melatonin triggers a series of events that lead to enhanced local triiodothyronine (T3) production in the medio-basal hypothalamus specifically under long days and ultimately drive the appropriate GnRH output at the median eminence. How T3 governs GnRH output is mostly unknown but neuronal populations that respectively produce KISS1 and RFRP3 appear to be involved. However, while the role of KISS1 as a major GnRH secretagogue is undisputed, the function of RFRP3 in the control of (seasonal) breeding remains enigmatic, with conflicting results hinting at elusive mechanisms. Therefore, we launched an extensive series of experiments in sheep, aimed at invalidating the NPVF gene, which encodes RFRP3, using CRISPR-Cas9 technology. Here, we report on the generation of six sheep for which the NPVF gene has been successfully edited. Four of these animals bear at least one allele expected to behave as a null and constitute founders for distinct ovine lines. These founder sheep will now enter a standard breeding scheme in order to obtain male and female homozygotes for distinct mutations. These animals are expected to provide a clear delineation of the function of RFRP3 in seasonal breeding.